Effect of β-adrenergic agonists on urea recycling by cattle fed varying levels and forms of nitrogen supplementation - Brake, Derek William (Kansas State University, 2009)
Two experiments analyzed effects of zilpaterol-HCl and nitrogen supplementation in the form of either dried distiller’s grains with solubles (DDGS) or urea fed to steers. In Experiment 1, steers were fed corn-based diets: control (CON; 10.2% CP), urea (UREA; 13.3% CP), or DDGS (14.9% CP). Nitrogen intake differed among treatments (99, 151, and 123 g/d for CON, DDGS, and UREA). Urea-N synthesis tended to be greater for DDGS (118 g/d) than for UREA (86 g/d), which tended to be greater than CON (52 g/d). Urinary urea-N excretion was greater ([italics]P[italics]<0.03) for DDGS (35.1 g/d) and UREA (28.6 g/d) than for CON (12.7 g/d). Gut entry of urea-N (GER) was numerically greatest for DDGS (83 g/d), intermediate for UREA (57 g/d), and least for CON (39 g/d). Urea-N returned to the ornithine cycle tended to be greater for DDGS (47 g/d) than for UREA (27 g/d) or CON (16 g/d). The percent of microbial N flow derived from recycled urea-N tended ([italics]P[italics]=0.10) to be greater for DDGS (35%) than for UREA (22%) or CON (17%). The percent of urea production captured by ruminal bacteria was greater ([italics]P[italics]<0.03) for CON (42%) than for DDGS (25%) or UREA (22%). Experiment 2 diets were identical to those used in Experiment 1. In addition, steers were also fed either 0 or 60 mg/d zilpaterol-HCl. Dietary CP was 9.6, 12.4, and 13.7% for CON, UREA, and DDGS, respectively. Zilpaterol increased ([italics]P[italics]<0.01) total DMI and N intake; however, zilpaterol did not affect urea entry rate ([italics]P[italics]=0.80) or GER ([italics]P[italics]=0.94). Urea entry rate and GER were numerically greater for DDGS than CON and UREA. In conclusion, zilpaterol did not influence urea entry rate or GER. This lack of response in the face of greater N intake was interpreted to suggest that zilpaterol may reduce urea production and GER at constant N intake.
Keywords: Urea recycling; Nitrogen; Cattle; β-adrenergic agonists; Distiller's grains with solubles; Corn; Agriculture, Animal Culture and Nutrition (0475); Chemistry, Agricultural (0749); Health Sciences, Nutrition (0570)